The Use of Augmented Reality in Teaching Islamic History to Millennial Students - Fitria Puji Atma dewi; Supriyanti Supriyanti (LP3M Pascasarjana STAI Ibnurusyd, 2025)
This study aims to examine the effectiveness of using Augmented Reality (AR) technology in teaching Islamic history to millennial generation students. The background of the study is based on the low interest and involvement of students in teaching Islamic history delivered conventionally. Using a quantitative approach through a quasi-experimental design, students were divided into two groups: the experimental group used AR media, while the control group used traditional learning methods. Data were collected through comprehension tests, learning motivation questionnaires, and observations of student involvement. The results showed that the use of AR significantly improved students' cognitive understanding, motivation, and involvement in the learning process. AR allows visualization of historical events in three dimensions and interactively, making learning more contextual, interesting, and enjoyable. This study concludes that AR is an effective learning medium for teaching Islamic history in the digital era. These findings are expected to be a reference for educators in designing innovative technology-based learning strategies.